Study of Diffusion of the Subject ‘Anthropocene’ over Different Disciplines: Quantitative Analysis by a New Indicator - Paul, Swapan; Dutta, Bidyarthi (Journal of Information and Knowledge, 2025)
This study applies S.R. Ranganathan’s APUPA (Alien-Penumbral-Umbral-Penumbral-Alien) pattern to classify research in the Anthropocene, an interdisciplinary field addressing human impact on Earth’s systems. The study introduces the Publication Fall Index (PFI) as a quantitative tool to distinguish between core and allied subjects, examining shifts in research focus over four periods: 2001-2005, 2006-2010, 2011-2015, and 2016-2020. Using bibliographic data from the Scopus database, the analysis identifies key subject areas like Earth and Planetary Sciences, Environmental Science, and Social Sciences while observing the rise of allied fields such as Engineering and Biochemistry. The methodology integrates the APUPA pattern with the PFI to map the evolution of core subjects, applying a structured framework for analysing the prominence and decline of research topics. The findings reveal significant shifts, particularly the increasing importance of technological fields such as Engineering from 2011-2020, highlighting the growing intersection between technology and environmental studies. This study’s originality lies in its contemporary application of Ranganathan’s traditional classification system, demonstrating its adaptability to modern, interdisciplinary research. The combination of APUPA and PFI provides valuable insights into subject diffusion within the Anthropocene, offering a robust methodology for navigating complex academic fields in the digital age.